Negotiation of Islamic Identity in Mencari Hilal Movie Subtitles Translation into English - Mukminin, Muhamad Saiful; Muhhit, Ahmad Abdul; Putra, Libra Dui; Ahmed, Aqeel (Indonesian literature Program, Faculty of Humanities, Diponegoro University, 2025)
The present research aims to analyze the negotiation of Islamic identity in the English translation of Mencari Hilal movie subtitles. The qualitative descriptive method is used to uncover the underlying patterns and nuances in translation, especially in texts with cultural and religious significance. The research data consists of instances of Islamic identity manifested in words and phrases found in the movie subtitles. The primary data source is the bilingual subtitle texts of Mencari Hilal, containing both the original Indonesian dialogue and their English translations. Data collection is carried out using the observation-note taking technique, which involves systematic reading and documentation of relevant translation instances. Data analysis follows the interactive model, which includes data reduction, data display, and conclusion drawing. The study identifies ten negotiation patterns in the subtitle translation of Mencari Hilal, reflecting efforts to adapt Islamic identity into the English cultural context. These patterns include religious commemoration, supernatural beings, religious constructions, religious artifacts, moral and ethical criteria, specialized religious activities, owner of religion, eschatology, religious events, and religious personages. These findings have significant implications for translation studies, particularly in translating texts with religious and cultural nuances. Negotiation in translation can shape audience perceptions of Islamic identity in the film.